P823 Comparison of copan urispongetm to colli-pee for the collection of urine for HPV detection with molecular assays. (14th July 2019) - Castriciano, Santina; Martinelli, Marianna
Abstract : Background: Urine specimen collection is non-invasive and better accepted by patients for HPV and STI screening. The Copan UriSponge TM, a Liquid Based Microbiology device, used for urine collection for culture and molecular assays. It consists of a leak-proof tube with a screw cap containing a plastic stick with sponges attached that absorb and retain the urine sample during transport preventing bacterial overgrowth. The objective of this study was to compare the UriSponge TM (US) to the Colli-Pee (CP) (Novosanis) urine devices for self-collection of first void urine (FVU) for the detection of HPV with the Seegene AnyplexII™-HPV28-assay. Methods: FVU, from 72 patients with a recent diagnosis of cervical dysplasia, attending the Gynecology clinic for colposcopy. 20 ml of first-void urine were collected using Colli-Pee TM and an additional aliquot of urine was collected in sterile containers to saturate UriSponge TM . Nucleic acids were extracted by NucliSENS easyMAG (bioMrieux) from US and CP urine. HPV detection was performed using AnyplexII TM HPV28-Assay. Sample cellularity was evaluated with a quantitative real-time PCR detecting human CCR5 gene. Results: Out of 72 urines tested 24 (33.3%) were positive for HR-HPV, 16 (22.2%) for HR+LR, 8 (11.1%) for LR and 24 (22.2%) were negative from both US and CP. Comparable cellularity was present in US and CP with a mean value of 2.09E+06. Optimal concordance for all HR- HPV genotypes compared to cervical sample was demonstrated for US and CP. HPV 16, 18, 51 and 31 were most frequently HR-HPV genotypes. Conclusion: Data obtained in this study demonstrated that the Copan UriSponge TM detected all HR-HPV positive samples and good cellularity compared to the cervical swab when compared to the Novosanis Colli-Pee TM using the Seegene Anyplex TM II HPV28 assay. The UriSponge TM is easy to use for urine self-collection, its not bulky, can be conveniently shipped by mail at a relatively low cost. Disclosure: No significant relationships.